Cisplatin Ototoxicity Blocks Sensory Regeneration in the Avian Inner Ear - Slattery, Eric L. (Society for Neuroscience, 2010)
Cisplatin is a chemotherapeutic agent that is widely used in the treatment of solid tumors. Ototoxicity is a common side effect of cisplatin therapy and often leads to permanent hearing loss. The sensory organs of the avian ear are able to regenerate hair cells after aminoglycoside ototoxicity. This regenerative response is mediated by supporting cells, which serve as precursors to replacement hair cells. Given the antimitotic properties of cisplatin, we examined whether the avian ear was also capable of regeneration after cisplatin ototoxicity. Using cell and organ cultures of the chick cochlea and utricle, we found that cisplatin treatment caused apoptosis of both auditory and vestibular hair cells. Hair cell death in the cochlea occurred in a unique pattern, progressing from the low-frequency (distal) region toward the high-frequency (proximal) region. We also found that cisplatin caused a dose-dependent reduction in the proliferation of cultured supporting cells as well as increased apoptosis in those cells. As a result, we observed no recovery of hair cells after ototoxic injury caused by cisplatin. Finally, we explored the potential for nonmitotic hair cell recovery via activation of Notch pathway signaling. Treatment with the γ-secretase inhibitor N-[N-(3,5-difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester failed to promote the direct transdifferentiation of supporting cells into hair cells in cisplatin-treated utricles. Taken together, our data show that cisplatin treatment causes maintained changes to inner ear supporting cells and severely impairs the ability of the avian ear to regenerate either via proliferation or by direct transdifferentiation.